مدى توافر الخصائص الريادية لدى القادة الاداريين: دراسة استطلاعية لآراء عينة من رؤساء الأقسام العلمية في جامعة الموصل - د. سلطان احمد خليف النوفل; د. نبال يونس محمد; صبا محمد نجيب (PROSPECTIVE RESEARCHES, 2023)
Environmental changes have made the managerial leadership seek the best methods to cope with those changes aridest to control them. Thus, the leadership style is one of the methods that have been adopt believing that it is the most effective tool for developing a group of facilities to interpret the ideas and concepts in a real situation. This demands that certain characteristics and features should be available to represent these styles in both form and content. Accordingly, the present study has set the following questions: 1- Do managerial leaders in organizations Sample study have a concept of leadership and its requirements? In addition, what are these characteristics available? The present study has also has reached a group of conclusions such as: 1- The availability of some Entrepreneurship Characteristics and characteristics in the personality of some of the leaders in the organizations under study though there some variations and differences in the values attained. 2- There were some real and existing of certain matters that represent the Entrepreneurship Characteristics and characteristics in forming a hierarchal chain other than other characteristics. This means that taking into consideration some waste when adopting and commencing any behavior at work was the most common contributing factor. This means that there could be a drawback in other factors. This condition has behalf of Mr. Henry Ford who was seventy bankrupt until he reached his success in developing his well-known company.